Augmented Reality, Virtual Reality, and Computer Graphics c - De Paolis, Lucio Tommaso; Bourdot, Patrick; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
The 2-volume set LNCS 12242 and 12243 constitutes the refereed proceedings of the 7th International Conference on Augmented Reality, Virtual Reality, and Computer Graphics, AVR 2020, held in Lecce, Italy, in September 2020.* The 45 full papers and 14 short papers presented were carefully reviewed and selected from 99 submissions. The papers discuss key issues, approaches, ideas, open problems, innovative applications and trends in virtual reality, augmented reality, mixed reality, 3D reconstruction visualization, and applications in the areas of cultural heritage, medicine, education, and industry. * The conference was held virtually due to the COVID-19 pandemic.
Virtual Reality -- Augmented Reality -- Mixed Reality -- 3D Reconstruction and Visualization.
Keywords: Image processing -- Digital techniques; Computer vision; 9; Computer engineering; Artificial intelligence; Software engineering; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Communication Networks; Computer Engineering and Networks; Artificial Intelligence; Software Engineering